Pemberdayaan Usaha Masyarakat Melalui Pelatihan Digitalisasi UMKM Oleh Mahasiswa KKN Kolaboratif UPN “Veteran’ Jawa Timur - Cavine One Happy Panjaitan; Kalvin Edo Wahyudi; Novita Wahyu Ningtias; Fiola Febriani; Gyta Adhelia Putri Sekarwangi (Abimanyu : Jornal of Community Engagement, 2025)
Increasing skills and marketing access for MSME owners, including Women Headed Families (PEKKA), is very important to improve their welfare. In Menampu Village and Sabrang Village, MSMEs face challenges in business management and marketing digitalization. The "Independent, Empowered and Contributing Women (MEDIASI)" program and digital marketing training by KKN students focuses on education related to digital marketing, optimizing social media and e-commerce platforms. The results of the activities show increased capabilities in product photography techniques and digital media management, which contribute to market expansion and product competitiveness. This program creates awareness of the importance of digitalization in business sustainability and is expected to continue to encourage sustainable economic growth with ongoing assistance.